ANALISIS YURIDIS KEPEMILIKAN HAK ATAS TANAH YANG DI PROLEH BERDASARKAN AKTA JUAL BELI YANG BERSUMBER DARI PPJB DAN AKTA KUASA JUAL YANG TELAH DI BATALKAN ( STUDI PUTUSAN MAHKAMAH AGUNG NOMOR 1681K/Pdt/2015 ) - MUJIB MEDIO ANNAS (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1. Prof. Dr. Muhammad Yamin, SH, MS, CN2. Prof. Dr. Syafruddin Kalo, SH, MHum3. Prof. Dr. Saidin, SH, MHum According to Article 37 paragraph 1 of the government regulation no. 24/1997 on Land Title Registration, it is stated that the transfer of land title and ownership rights over a unit of flats can only be registered if it is made in a deed by a Land Title Registrar. Every transfer of land title is obliged to be registered to the local National Land Office, and its registration has to meet all provisions in the Regulations of Ministry of Agrarian/Head of National Land Office No. 3/1997 on the Provisions of Implementation of the Government Regulations No. 24/1997 on Land Registration. However, in practice, land title transfer is frequently preceded by a Sale and Purchase Contract and Power of Attorney to Sell. This research studies how the legal status of the sale and purchase contract and power of attorney to sell is in the land title transfer pursuant to the prevailing laws and regulations, how the legal consequences for the land title that is transferred based on a sale and purchase deed sourced from a sale and purchase contract and power of attorney to sell that has been annulled, and how the analysis of the Verdict of the Supreme Court No. 1681k/pdt/2015 related to the land title transfer based on a sale and purchase deed sourced from a sale and purchase contract and power of attorney to sell that has been annulled. The analysis of the Verdict of the Supreme Court No. 1681k/pdt/2015 pronouncing that the legal action made by the Cassation Applicant/Plaintiff and I Nyoman Widajaya had legal defects and is null and void before the law has been appropriate. In relation to the sale and purchase contract made for the land and building.Keywords: Ownership Rights over Land, Annulled Deed